Itaconate ameliorates autoimmunity by modulating T cell imbalance via metabolic and epigenetic reprogramming - Kuniyuki Aso; Michihito Kono; Masatoshi Kanda; Yuki Kudo; Kodai Sakiyama; Ryo Hisada; Kohei Karino; Yusho Ueda; Daigo Nakazawa; Yuichiro Fujieda; Masaru Kato; Olga Amengual; et al. (Nature Communications, 2023)
Dysregulation of T cell homeostasis is known to contribute to the immunopathology of autoimmune diseases. Here the authors show that itaconate impacts autoimmune pathology by altering T cells via modulation of metabolic and epigenetic programs.